Utilization of paper waste as growing media for potted ornamental plants - Chrysargyris, Antonios; Stavrinides, Menelaos; Moustakas, Konstantinos; Tzortzakis, Nikos G. (My University, 2018)
Abstract: The paper industry generates significant quantities of waste. The recycling of paper waste (PW) for peat replacement in growing media for ornamental plants cultivation was studied. Five ratios of PW–peat (0%, 10%, 30%, 50% or 100% v/v) were evaluated for marigold (Calendula officinalis L.), petunia (Petunia × hybrita L.) and matthiola (Matthiola incana L.) plants. Addition of PW increased the substrate pH and mineral content but decreased the air-filled porosity. In marigold, the use of 100% PW reduced plant height, plant diameter, fresh weight for both leaves and flowers and the total number of flowers produced compared to the control (100% peat). In matthiola, 100% PW reduced plant height, whereas the addition of PW even at 10% decreased plant diameter and fresh weight (biomass) but increased dry matter content. Petunia plants grown in 100% PW exhibited lower growth (plant height and diameter), whereas adding ≥ 50% of PW decreased plant fresh weight. The total number of flower buds and open flowers increased (more than twofold) on plants grown in 30% PW compared to the control substrate, indicating flower earliness. Plant leaf chlorophyll content (Chl a, Chl b, total Chl) decreased as the PW ratio increased. Total phenolics and antioxidant capacity as well as plant damage index and enzymes scavenging activities varied among species. Mineral content fluctuated among species with decreases of N and P in plants grown in PW mixtures while matthiola showed phytotoxicity symptoms. The present study suggests that peat can be substituted by up to 30% of PW for marigold and petunia for potting culture, but not for matthiola, as the physicochemical properties of the substrate need further improvement.
Keywords: Enzyme activity; Ornamental; Paper waste; Peat; Recycling; Seedlings